The Relationship Between Human Capital and the Regional Economy Productivity - Hendarmin, Hendarmin; Kartika, Metasari (JEJAK: Jurnal Ekonomi dan Kebijakan, 2019)
The aim of this study is to measure the impact of the human capital on the economic productivity level in provinces of Kalimantan Island. The data used in this study was a panel data from 5 provinces in Kalimantan Island within 2013-2017 time periods which its study finding was analyzed using panel data regression analysis with random effect approach. The study finding explains that the human capital, measured by the education level which is the average of years of education, the health level which is life expectancy and investment has a positive effect on the productivity level of the regional economy. The analysis result also shows that the health variable has a bigger magnitude compared to the education and physical capital investment variables. Based on the result, it can be concluded that the effect of human capital is very important in increasing economic productivity in the region.